Influence of protectionist customs policy on the concentration and development of heavy industry exemplified by the steelmaking sector in Germany (Economic and Political Thought, 2017)
Historically developed countries (USA, France, and UK) have not beendeveloped on the basis of the principles of free trade, but protectionist policy.Still today, it is advisable that such a policy is good for developing countries.The necessity to protect a domestic market has been discussed for hundredsof years. Beside the main current of classical economics glorifying inter aliafree trade, with the development of capitalism and schools of economic thought,alternative schools and currents indicating the need of protection cameinto being. Protectionist policy may adopt different forms, including tariffprotection discussed in the article, especially the conception of infant industry,optimal duty as well as subsidies for producers, export promotion etc.Despite rather common criticism of tariff protection, it should be recognisedthat the assumptions described by F. List and A. Hamilton in the 19th centuryhave solid theoretical foundations and many contemporary economists(e.g. P. Krugman) demonstrates the advantages of such policy. The author,with the use of theoretical models, assesses the influence of educational dutytaking into consideration social welfare in a (small and big) country imposingtariffs as well as global welfare. He also uses statistical data concerning theUnited Kingdom, the USA, Japan and Germany in particular. The example ofdevelopment, protection and dominance of steelmaking industry in the NaziGermany is especially meaningful. The author uses econometric (cliometric)modeling to demonstrate the relationship between the rapid increase in steelproduction and the German government’s protectionist policy. The possibilityof applying tariff protection in the contemporary economy, especially in caseof developing countries, remains an important issue.